Transdisciplinary integrated curriculum: An analysis of teacher experiences through a design model within the framework of IB-PYP - Gürkan, Burcu (Ozgen Korkmaz)
The purpose of the study is to examine the positive and negative experiences of teachers through a model in the process of designing a transdisciplinary integrated curriculum within the framework of IB-PYP. The design of the study included a holistic, multiple-case approach. The study was carried out with 50 teachers, among which 7 (14%) are male and 43 (86%) are female, in the IBEC teacher curriculum at a university in Turkey in the 2018-2019 spring and 2019-2020 fall academic terms. IBEC was given in Istanbul, Ankara, and Gaziantep cities in Turkey. The data were collected with researcher diary, focus group interviews and reflective writings, and analyzed through content analysis. In the study in which the transdisciplinary integrated curriculum was designed using a model, it was observed that the model brought systematic approach to teachers. The integrated curriculum design was realized through the cooperation of teachers from different branches, which proved to be efficient to cooperate with different disciplines. Emphasizing that they had difficulty in selecting practices for planning and evaluating the teaching process, the participant teachers also affirmed that specifically these stages developed them professionally. In designing the program, teachers also developed coping skills. It is understood that the brainstorming technique relieved teachers' challenges. It was found that teachers' experiences were of significance in effective design of the integrated programs. School-based program development, collaborative work, and the ability to meet the needs of different disciplines with a common mechanism were become evident over time. © 2021, Ozgen Korkmaz. All rights reserved.
Keywords: Integrated curriculum; Teacher education; Transdisciplinary instructional design